Publishing, politics, and culture the king's printers in the reign of James I and VI - Rees, Graham (Oxford University Press, 2009)
Based on hitherto unexplored and unpublished legal and business records, this study presents a full account of London printing firms in the reign of James I. In particular it examines the businesses of men associated with that crucial instrument of cultural production - the King's Printing House.